Diaspora Causatum: Enhancing Defense Diplomacy Through Alterations in Citizenship Laws - Ronny, Shabrina Amelia; Helda Risman; Waluyo, Surryanto Djoko (Technium Social Sciences Journal, 2020)
The paper aims to analyze how diasporas across the globe can become potential elements in enhancing their home country’s national interest. Through social aspects such as citizenship laws, engaging diasporas can be one way to broaden a state’s resources in its defense system. Comparative analysis and assessment are used to elaborate on how various countries – which possess a large number of diasporic communities along with comprehensive law systems that regulate its citizenship issues – are reflected upon and proposed for a modified model within Indonesia’s scope. The paper concludes that modification of the Indonesian citizenship law in accordance with the government’s strategic Defense Diplomacy is an effective way of enhancing sustainable ties with other countries. This research can be used within the government to consider diasporas as elements of national power. Other areas of study, such as defense studies and security studies, may also benefit. This research offers a unique way in altering Confidence Building Measure (CBM) mechanisms in the scope of Defense Diplomacy Studies that will enhance good relations and comprehensively establish synergies between public diplomacy and defense diplomacy en bloc.